Monopoiesis in humans and mice. (21st September 2018) - Kawamura, Shunsuke; Ohteki, Toshiaki
Abstract: Monocytes are a widely conserved cell population in vertebrates with important roles in both inflammation and homeostasis. Under both settings, monocytes continuously arise from hematopoietic progenitors in the bone marrow and, on demand, migrate into tissues through the bloodstream. Monocytes are classified into three subsets—classical, intermediate and non-classical—based on their cell surface expression of CD14 and CD16 in humans and Ly6C, CX3 CR1 and CCR2 in mice. In tissues, monocytes differentiate further into monocyte-derived macrophages and dendritic cells to mediate innate and adaptive immune responses and maintain tissue homeostasis. Recently, the progenitors that strictly give rise to monocytes were identified in both humans and mice, thereby revealing the monocyte differentiation pathways.